Hubungan sepsis neonatorum, BBLR dan asfiksia dengan kejadian ikterus pada bayi baru lahir - Widiawati, Susi (Riset Informasi Kesehatan, 2017)
ABSTRACT   Background : Neonatal Jaundice can be both physiological and pathological, several factors could be due to neonatal sepsis, low birth weight and asphyxia. The purpose of this study was to look at the relationship neonatal sepsis, low birth weight and asphyxia with the incidence of neonatal jaundice in newborns aged 0-7 days in hospitals RadenMattaher Jambi 2016. Methods : This study is a quantitative research, case-control approach. The population of cases in this study were 102 babies diagnosed with jaundice and population control as many as 167 babies who are undiagnosed jaundice. Sample cases as much as 65 babies diagnosed with jaundice and a control sample of 65 infants not diagnosed jaundice, sampling technique purposive sampling technique using matching sex. The instrument used was a checklist sheet. Data was analyzed by univariate and bivariate using chi-squere. Results : The results of the univariate analysis of 65 known infant jaundice (50.0%). Babies who neonatal sepsis in 69 (53.1%). Infant low birth weight by 70 (53.8%) and neonatal asphyxia by 74 (56.9%). There is a relationship between neonatal sepsis with an OR of 3.352 p-value (0.002), there is a relationship LBW with OR of 8.820 p-value (0.000) and there is a relationship asphyxia with OR of 4.900 p-value (0.000) in the incidence of neonatal jaundice in newborn birth age 0-7 days. Conclusion : Mothers need to get health education about the importance of prenatal care, to obtain information from health professionals about the development of the fetus, newborn care to prevent the occurrence of neonatal jaundice.   Keywords: asphyxia, low birth weight, jaundice and neonatal sepsis